Spare Bed-Room - Zwartjes, Frans (The Netherlands, 1970)
The film follows two sombre personages who are engaged in a claustrophobic game of attraction and repulsion.
Black and White
No Dialogue
Verzio Film Festival Submission
Keywords: Experimental films